Expression of the p53 homologue p63α and ΔNp63α in the neoplastic sequence of Barrett's oesophagus: correlation with morphology and p53 protein. Issue 5 (1st November 2001) - Hall, P A; Woodman, A C; Campbell, S J; Shepherd, N A
Abstract : BACKGROUND: While loss of p53 function is a key oncogenic step in human tumorigenesis, mutations of p53 are generally viewed as late events in the metaplasia-dysplasia-adenocarcinoma sequence of Barrett's oesophagus. Recent reports of a series of genes (p63, p73, and others) exhibiting close homology to p53 raise the possibility that abnormalities of these p53 family members may exert their influence earlier in the sequence. AIM: Following recent characterisation of expression of p63 and a major isoform ΔNp63 by generation of an antiserum that recognises p63 isoforms, but not p53, our aim was a comparative study of expression of p63 protein and p53 protein in a morphologically well defined biopsy series representative of all stages of the metaplasia-dysplasia-carcinoma sequence in Barrett's oesophagus. METHODS: A series of 60 biopsy cases representing normal oesophagus through to invasive adenocarcinoma were stained, using immunohistochemistry, with antibodies to p63 and p53. All biopsies derived from patients with endoscopic and histopathological substantiation of a diagnosis of traditional/classical Barrett's oesophagus. RESULTS: There was exact concordance in p53 and p63 expression in more advanced forms of neoplasia, high grade dysplasia, and invasive adenocarcinoma, while p63, but not p53, was detected in the proliferative compartment of some non-neoplastic oesophageal tissue, in both squamous mucosa and in the non-neoplastic metaplastic glandular epithelium. CONCLUSIONS: In neoplastic Barrett's oesophagus there is upregulation of both p63 and p53 while p63 isoforms may well have an important role in epithelial biology in both non-metaplastic and metaplastic mucosa of the oesophagus. While abnormalities of p53 function represent an indisputable and critical element of neoplastic transformation, other closely linked genes and their proteins have a role in both the physiology and pathophysiology of the oesophageal mucosa.